Generalized invexity and mathematical programs - Joshi, Bhuwan Chandra; Mohan, Rakesh; Pankaj (Yugoslav Journal of Operations Research, 2021)
In this paper, using generalized convexity assumptions, we show that Mstationary condition is sufficient for global or local optimality under some mathematical programming problem with equilibrium constraints(MPEC). Further, we formulate and study Wolfe type and Mond-Weir type dual models for the MPEC, and we establish weak and strong duality theorems.